The effect of self-care education on adherence to treatment in elderly patients with heart failure: A randomized clinical trial - Saeed Eimer; Gholam Reza Mahmoodi-Shan; Ali Akbar Abdollahi (Iranian Journal of Nursing and Midwifery Research, 2023)
Background: Noncompliance with treatment in the elderly with Heart Failure (HF) may result in a lack of recovery, a decrease in longevity, rehospitalization, and additional costs. Therefore, this study was conducted to determine the effect of self-care education on adherence to treatment among elderly patients with HF. Materials and Methods: This study was a parallel clinical trial on 90 elderly people over 60 years of age who were hospitalized in cardiac wards. Data were collected using a demographic characteristics form and the adherence to treatment questionnaire. Individuals who met the study inclusion criteria were randomly allocated to the intervention and control groups. The intervention group training was performed before and after discharge. The adherence to treatment questionnaire ↱was completed again by both groups 2 months after discharge. Data were analyzed using Chi-squared test; ex. (?2 = 3.95, df = 1, p = 0.046), paired and independent t-tests, and analysis of covariance. Results: The mean (standard deviation) total score of adherence to treatment in the intervention group was 39.71 (4.51) and 78.72 (10.47) before and after the self-care education, respectively. Paired t-test showed a significant difference in both groups after the intervention compared to before the intervention, and independent t-test showed a significant difference between the groups after the intervention (p = 0.001). Conclusions: Self-care education before discharge and home-based education were effective in promoting adherence to treatment among patients with HF. Therefore, self-care education before discharge may improve adherence to treatment among elderly patients with HF.